Transparent patch antenna design using aluminium-doped zinc oxide (ZnO:A1) / Mohd Shahar Mohd Saad - Mohd Saad, Mohd Shahar (2014)
A transparent antenna using Aluminum-doped Zinc Oxide (ZnO:AI) or AZO as a radiating component and glass with an AZO ground as a substrate. The simulation using CST Microwave software based on a simple micro-strip patch design, calculated to get the resonance frequency of 2.4 GHz for WLAN application. The low resistivity value of AZO (1.44x10" Q-cm) when converted to conductivity value, G = 6.9444 x 10 S/m will be used in CST Microwave for simulation.